2011
DOI: 10.1248/yakushi.131.1061
|View full text |Cite
|
Sign up to set email alerts
|

New Strategy of Adult T-cell Leukemia Treatment Targeted for Anti-tumor Immunity and a Longevity Gene-encoded Protein

Abstract: Adult T-cell leukemia-lymphoma (ATL) is an aggressive peripheral T-cell neoplasm with a poor prognosis, developing after long-term infection with human T-cell leukemia virus-1 (HTLV-1). Multiple factors (e.g., virus, host cells, epigenetic aberrations, and immune factors) have been implicated in the development of ATL, although the underlying mechanisms of leukemogenesis have not been fully elucidated. Despite recent progress in both chemotherapy and supportive care for hematological malignancies, the prognosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…New strategies for the therapy and prophylaxis of ATL ( e.g. , vaccines and novel molecular target agents) are still required 5, 8–10…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…New strategies for the therapy and prophylaxis of ATL ( e.g. , vaccines and novel molecular target agents) are still required 5, 8–10…”
mentioning
confidence: 99%
“…6,7 New strategies for the therapy and prophylaxis of ATL (e.g., vaccines and novel molecular target agents) are still required. 5,[8][9][10] Histone deacetylase (HDAC) inhibitors are a new class of antitumor agent that is currently undergoing intensive pre-clinical and clinical testing. 11 Depsipeptides (FR901228, FK228), a member of the cyclic peptide class of HDAC class I/II inhibitors, have shown cytotoxic effects on several malignant lymphoid cell lines, 12 including HTLV-1-infected T-cell lines.…”
mentioning
confidence: 99%
“…A study by Herth et al (18) previously concluded that thalidomide maintenance therapy drives the maturation of T cells toward a memory phenotype, however, compromises antigen-specific immunity. Additionally, the decreased frequency and function of CD8 + T cells has been previously described for T-cell lymphoma (19). It was hypothesized that the cause of IgA pemphigus in the present patient may have been a combination of the immunological imbalance, which was caused by the blood-lymphatic system cancer, and thalidomide-induced immunomodulatory effects.…”
Section: Discussionmentioning
confidence: 65%
“…[2][3][4] Cluster of differentiation (CD) molecules are expressed on most normal cells. However, CD molecules are often overexpressed on tumor cells.…”
Section: Introductionmentioning
confidence: 99%